2022 ACM Conference on Fairness, Accountability, and Transparency 2022
DOI: 10.1145/3531146.3533218
|View full text |Cite
|
Sign up to set email alerts
|

“There Is Not Enough Information”: On the Effects of Explanations on Perceptions of Informational Fairness and Trustworthiness in Automated Decision-Making

Abstract: Automated decision systems (ADS) are increasingly used for consequential decision-making. These systems often rely on sophisticated yet opaque machine learning models, which do not allow for understanding how a given decision was arrived at. In this work, we conduct a human subject study to assess people's perceptions of informational fairness (i.e., whether people think they are given adequate information on and explanation of the process and its outcomes) and trustworthiness of an underlying ADS when provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Thus, procedural fairness can be increased even if the decision outcome is biased by using appropriate input features and ensuring people can appeal an ADM decision. We further find that five studies also included interactional fairness, and six studies investigated informational fairness (Acikgoz et al, 2020;Binns et al, 2018;Schoeffer et al, 2021). These studies zoom into the decision process and emphasize its social aspects, such as treating individuals with respect and receiving an explanation for an ADM decision (Schlicker et al, 2021).…”
Section: Concepts Of (Algorithmic) Fairnessmentioning
confidence: 82%
See 3 more Smart Citations
“…Thus, procedural fairness can be increased even if the decision outcome is biased by using appropriate input features and ensuring people can appeal an ADM decision. We further find that five studies also included interactional fairness, and six studies investigated informational fairness (Acikgoz et al, 2020;Binns et al, 2018;Schoeffer et al, 2021). These studies zoom into the decision process and emphasize its social aspects, such as treating individuals with respect and receiving an explanation for an ADM decision (Schlicker et al, 2021).…”
Section: Concepts Of (Algorithmic) Fairnessmentioning
confidence: 82%
“…After being asked, "Who would, according to you, make a fairer decision: a human or artificial intelligence/computer?," 54% of respondents answered that they believed AI makes fairer decisions (compared to 33% for humans) (Helberger et al, 2020). Schoeffer et al (2021) investigated open-ended questions and also found that respondents perceived ADM as less biased than HDM. Other studies support this general finding in university admission decisions (Marcinkowski et al, 2020) and algorithmic work assignments (Bai et al, 2020).…”
Section: Comparative Effects (Hdm Vs Adm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Counterfactual explanation (CFE) [44] aims to identify minimal changes required to modify the input to achieve a desired prediction and provides insights into why a model produces a certain prediction instead of the desired one. CFEs can help understand the underlying logic of certain predictions [31], detect the inherent model bias for fairness [19], and provide suggestions to users who receive adverse predictions [17,39]. Therefore, CFEs can be adopted in broad applications of healthcare, finance, education, justice, and other domains.…”
Section: Introductionmentioning
confidence: 99%